Etika Bermedia: Menyebar Foto dan Video Tanpa Izin Termasuk Melanggar Privasi - Nanda Elma Fitriani; Ela Indah Dwi Syayekti; Muhammad Syarif Hidayatullah (Academic Journal of Da'wa and Communication, 2023)
This study aims to determine ethics in media including taking photos or videos that include privacy. Not everyone likes it when their photos appear on social media. This will realize the importance of upholding ethics in media. The method used in this study is library research by collecting information and data with the help of various kinds of existing materials such as documents, books, journals, articles and so on. The results of this study show that media ethics are very important today. The right to privacy is often forgotten by media users, especially when taking pictures or recording others without permission. The rules of social media are in fact not in harmony with conditions on the ground. Many violations occur, for example the distribution of photos and videos of someone without permission to the person concerned. It is expected that users will be wiser in addressing the boundaries needed when mediating. In addition, media providers should provide features that support the security and privacy of their users.